2013
DOI: 10.1177/1757975913501911
|View full text |Cite
|
Sign up to set email alerts
|

Tracking MPOWER in 14 countries: results from the Global Adult Tobacco Survey, 2008–2010

Abstract: Abstract:Background: The World Health Organization (WHO) MPOWER is a technical package of six tobacco control measures that assist countries in meeting their obligations of the WHO Framework Convention Tobacco Control and are proven to reduce tobacco use. The Global Adult Tobacco Survey (GATS) systematically monitors adult tobacco use and tracks key tobacco control indicators. Methods: GATS is a nationally representative household survey of adults aged 15 and older, using a standard and consistent protocol acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…A slightly higher (39.3%) smoking prevalence has been found in the Russian Federation (GATS 2009) 1819 Among the European Union countries that released GATS results, Poland (30.5%) and Romania (26.7%) had considerably lower smoking rates compared with Greece 18–20. In addition, results from GATS from two South Eastern Mediterranean Region countries, Egypt (19.7%) and Turkey (GATS 2012; 27.1%),18–20 also showed lower smoking rates.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A slightly higher (39.3%) smoking prevalence has been found in the Russian Federation (GATS 2009) 1819 Among the European Union countries that released GATS results, Poland (30.5%) and Romania (26.7%) had considerably lower smoking rates compared with Greece 18–20. In addition, results from GATS from two South Eastern Mediterranean Region countries, Egypt (19.7%) and Turkey (GATS 2012; 27.1%),18–20 also showed lower smoking rates.…”
Section: Discussionmentioning
confidence: 95%
“…19 Among the European Union countries that released GATS results, Poland (30.5%) and Romania (26.7%) had considerably lower smoking rates compared with Greece 18–20. In addition, results from GATS from two South Eastern Mediterranean Region countries, Egypt (19.7%) and Turkey (GATS 2012; 27.1%),18–20 also showed lower smoking rates. Regarding determinants of current smoking, our results showed that sex was a strong independent determinant of current smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The myriad health effects associated with smoking may call for the implementation of the World Health Organization’s Framework Convention on Tobacco Control mPOWER initiative in communities across America. 120 …”
Section: How To Improve Upon Intermediate and Poor CV Healthmentioning
confidence: 99%
“…However, tobacco being an addictive substance, most users struggle to quit and many only do so with behavioural and/or pharmacological support 6. According to Global Adult Tobacco Survey, more than 30% of smokers in LMICs attempted to quit in the previous year (15% in China) 7. However, in most countries in particular LMICs, cessation advice or services are not available 8.…”
mentioning
confidence: 99%